Sustainability Indicators: A Scientific Assesment - Tomas Hak, Bedrich Moldan (Island Press, 2006)
This comprehensive volume is essentials reading for anyone working professionally in the field of sustainability a masterful job of surveying the current state of the field from a global scientific perspective